Financial Protection in Health among the Elderly - A Global Stocktake - Patrick Hoang-Vu Eozenou; Sven Neelsen; Marc-Francois Smitz (Taylor & Francis Group, 2021)
Universal Health Coverage is one of the key targets of the Sustainable Development Goals and it implies that everyone can access the healthcare they need without suffering financial hardship. In this paper, we use a large set of household surveys to examine if older populations are facing different degrees of financial hardship compared to younger populations. We find that while differences in average age structures between countries are not systematically associated with higher financial risk related to out-of-pocket health expenditures, there are large differences in financial hardship between younger and older households within countries. Households with more elderly members are more likely to face catastrophic and impoverishing out-of-pocket health payments compared to younger households, and this age gradient is stronger for the poorest segments of the population. Making progress toward Universal Health Coverage will require extension and improved targeting of benefit packages and financial protection to meet the health needs of older adults, and especially the poorest and most vulnerable segments of elderly populations.